Manajemen Data Produksi Barang di PT. Tirta Gemilang Rahayu Menggunakan Jurnal Mekari - Hudori, Mahfuz; Azzahra, Alifia; Sari, Yesi Verdiana; Nuraini, Nuraini (LPPM ITEBA, 2024)
The financial transaction and inventory data management system at PT. Tirta Gemilang Rahayu is still manual, leading to data management inefficiency. This prompted the need for staff training in managing inventory data digitally using Jurnal Mekari. This activity aims to assist PT. Tirta Gemilang Rahayu staff in managing the company's inventory data digitally using Jurnal Mekari. This activity was conducted at PT. Tirta Gemilang Rahayu, involving 2 company staff and 3 Universitas Nahdlatul Ulama internship students. The methods used in this activity were lectures and practice sessions. The community service activity conducted at PT. Tirta Gemilang Rahayu demonstrated the effectiveness of implementing Jurnal Mekari in enhancing inventory data management efficiency and effectiveness. This, in turn, contributes to the smooth operation of the company.